Humanoid Robots like Tesla Optimus and the Future of Supply Chains: Enhancing Efficiency, Sustainability, and Workforce Dynamics - Mohammad Shamsuddoha; Tasnuba Nasir; Mohammad Saifuddoha Fawaaz (Automation)
Integrating futuristic humanoids like Tesla Optimus into supply chain operations represents groundbreaking automation and workforce efficiency innovation. This study investigates the potential of humanoids to address critical supply chain challenges, such as labor shortages, rising operational costs, and the demand for sustainable practices. Considering its ability to handle worker-intensive, hazardous, and repetitive duties, humanoids could offer an alternative to business challenges like inefficient operations, health and safety concerns, and worker shortages. Intelligent robotics plays an essential role in improving productivity, supporting sustainability, and transforming workforce dynamics as supply chains become increasingly complex. The study examines the effects of humanoids on workforce reallocation, manufacturing sustainability, and supply chain productivity. The current research reviews the usefulness, advantages, and downsides of integrating humanoids into supply chains. This study uses a mixed-method approach, incorporating case studies, qualitative productivity data, and expert interviews. According to Tesla, Optimus could significantly enhance supply chain efficiency by reducing error rates, streamlining workflows, and enabling 24/7 operations. It could also help meet sustainability goals by lowering waste and energy consumption. The study limits Tesla’s experience, modern technologies, and inadequate information from various industrial and geographical contexts. However, this study will be eye-opening for industries requiring such humanoid robots for their operations. Additional studies need to deal with factors like high implementation expenses, potential job displacement, and flexibility in changing supply chain demands. While focused on Tesla, this study provides insights that can inform broader applications of humanoid robotics in supply chains across industries. This study presents an in-depth review of humanoid involvement in developing future supply chain models. It also offers helpful knowledge that will assist industries in considering adopting comparable robotic integration as a strategic decision.